Advanced sports nutrition - Benardot, Dan 1949 (Human Kinetics, 2021)
"Advanced Sports Nutrition offers detailed nutrition guidance for the athlete. It is heavily referenced and supported by industry position stands, offering expert advice for athletes across all sports. It explains explain HOW to best fuel for exercise and WHY, backed up by the latest evidence. It includes tools such as pre-game nutrition strategy handouts that help the athlete apply the science for their own use"--